Genetic diversity of persimmon accessions introduced and surveyed in Spain - Badenes M.L.; Garcés A.; Romero C.; Llácer G.; Romero M.; Clavé J.; Rovira M. (First Mediterranean symposium on persimmon, 2002)
- The oriental persimmon (Japanese persimmon or kaki), Diospyros kaki L.f., is believed to have originated in China and was introduced from Japan into Europe, Brazil and the United States in the nineteenth century. Persimmon culture has become an alternative for fruit growers in Italy, Israel and Spain. However, there is some confusion concerning cultivar identification in non-Asian countries where the species has been introduced. Authenticating the identity of germplasm resources of persimmon would be of great value for breeding. RAPD markers were chosen for this study of persimmon germplasm resources in Spain. Nineteen markers were obtained from eight primers. Results suggest that RAPD technology is adequate for fingerprinting persimmon and the data is consistent with persimmon's hypothetical origins and adaptation history. By means of RAPD markers, a better identification of the European germplasm is available.
1. Mediterranean Symposium on Persimmon, 2001/11/23-24, Faenza (Italy)